Poultry by-product meal as dietary protein source for dourado, Salminus brasiliensis: an economic appraisal - Renan Antunes Donadelli; Fredy Armando Aguilar Aguilar; Daniel Yokoyama Sonoda; José Eurico Possebon Cyrino (Scientia Agricola)
ABSTRACT: The dourado, Salminus brasiliensis, a large, carnivorous, Neotropical, Characin, is highly regarded for fish farming and sport fishing alike. However, studies on the farming and husbandry of dourado are still scarce. This study evaluated the performance of dourado fed diets formulated so as to contain increasing levels of poultry by-product meal as a replacement for fish meal and aimed to identify the maximum level of replacement to maximize profit. The trial was set up in a closed recirculation system with controlled water quality (temperature 27 °C, dissolved oxygen 6.5 mg L−1, pH 7.4, and ammonia 0.25 mg L−1). Juvenile fish were stocked in tanks in a completely randomized design, acclimatized to system conditions and experimental diets, and then fed twice a day for 66 days with extruded, nutritionally complete diets (40 % digestible protein and 4020 kcal kg−1 digestible energy), formulated to contain 0, 20, 40, 60, 80 or 100 % poultry meal as a surrogate protein source for fish meal. Performance parameters – average weight gain, specific growth rate, feed consumption, feed conversion rate, protein efficiency rate, productive value of protein, energy retention rate, survival rate – did not differ (p > 0.05). To minimize the effects of influential data, the robust regression method was used and profit maximization analysis revealed that replacing 33.3 % of dietary fishmeal by poultry by-product meal maximizes profit in the farming of dourado.